The independent role of prenatal and postnatal exposure to active and passive smoking on the development of early wheeze in children. Issue 1 (10th March 2016) - Vardavas, C.I.; Hohmann, C.; Patelarou, E.; Martinez, D.; Henderson, A.J.; Granell, R.; Sunyer, J.; Torrent, M.; Fantini, M.P.; Gori, D.; Annesi-Maesano, I.; Slama, R.; et al.
Maternal smoking during pregnancy increases childhood asthma risk, but health effects in children of nonsmoking mothers passively exposed to tobacco smoke during pregnancy are unclear. We examined the association of maternal passive smoking during pregnancy and wheeze in children aged ≤2 years. Individual data of 27 993 mother–child pairs from 15 European birth cohorts were combined in pooled analyses taking into consideration potential confounders. Children with maternal exposure to passive smoking during pregnancy and no other smoking exposure were more likely to develop wheeze up to the age of 2 years (OR 1.11, 95% CI 1.03–1.20) compared with unexposed children. Risk of wheeze was further increased by children's postnatal passive smoke exposure in addition to their mothers' passive exposure during pregnancy (OR 1.29, 95% CI 1.19–1.40) and highest in children with both sources of passive exposure and mothers who smoked actively during pregnancy (OR 1.73, 95% CI 1.59–1.88). Risk of wheeze associated with tobacco smoke exposure was higher in children with an allergic versus nonallergic family history. Maternal passive smoking exposure during pregnancy is an independent risk factor for wheeze in children up to the age of 2 years. Pregnant females should avoid active and passive exposure to tobacco smoke for the benefit of their children's health. Prenatal and postnatal exposure to active and passive smoking independently increase early wheeze risk in children http://ow.ly/XZvQQ